TREND ANALYSIS OF AREA AND PRODUCTIVITY OF SORGHUM IN SOKOTO STATE, NIGERIA, 1993-2012 - Maikasuwa, M., A.; Ala, A.L. (European Scientific Journal, ESJ, 2013)
ï»¿ï»¿ï»¿ï»¿The study was carried out to examine trends in area and productivity of sorghum in Sokoto state, Nigeria from the period 1993-2012. Secondary data collected from the State Agricultural Development Programmes (ADPs) for the period 1993-2012 were used for the study. Exponential trend equations were fitted to area and productivity to examine their patterns of growth. The computed growth trend for area was negative (-0.015) and significant (P<0.05). The computed growth trend for productivity was positive (0.035) and significant (P<0.01). However, The quadratic time term indicated a stagnated growth in area and an accelerated growth in productivity. It was suggested that the process of decline in area should be reversed through expansion of area devoted to sorghum cultivation and the process of growth in productivity could be enhanced through increased use of advisory services and provision of input supports to the farmers engaged in the cultivation of sorghum